A Systematic Review on Cloud Computing - Haris, Mohammad; Khan, Rafiqul Zaman (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is the fastest growing technology in the IT world. It is an architecture which combined the concept of Virtualization technology with several computing paradigms such as Distributed computing, Utility computing, Grid computing etc. to achieve the goal of providing unlimited resources and services over the internet. Cloud computing uses the concept of pay as per use basis where users do not need to pay for infrastructure, installation and its maintenance. Anyone can access the desired service from cloud anytime, anywhere in the world on demand basis. This paper presents an overview of cloud computing along with Root of cloud computing, its evolution and a comparative study of Cloud with several other computing paradigm. It also highlights the characteristic, deployment and service model of cloud computing. The various benefits of cloud with its challenges and applications are also addressed in this paper